Active caseinate/guar gum films incorporated with gallic acid: Physicochemical properties and release kinetics. (December 2022) - Khan, Muhammad Rehan; Volpe, Stefania; Salucci, Emiliano; Sadiq, Muhammad Bilal; Torrieri, Elena
Abstract: Composite active films based on sodium caseinate/guar gum were prepared by the incorporation of gallic acid at different concentrations to investigate its effect on the structure, physicochemical properties, and the release kinetics from the film. The incorporation of gallic acid imparted changes in the FT-IR spectra. Water vapor permeability (WVP) of films decreased up to 21% after the incorporation of gallic acid in the film. The gallic acid released from the films GAI* 60 μg.ml−1, GAII* 250 μg.ml−1 and GAIII* 650 μg.ml−1 was 67%, 32% and 30% respectively. Similarly, the diffusion coefficient was also affected by an increase in the concentration and was: 8.10 × 10 −12 m 2 s −1, 6.23 × 10 −12 m 2 s −1, and 4.5 × 10 −12 m 2 s −1 for GAI, GAII and GAIII films respectively. Molecular docking suggested the potential inactivation of oxidative enzymes due to binding of gallic acid near their active sites. Therefore, gallic acid releasing films maybe considered as an active food packaging for fruits and vegetables (F&V). Highlights: Physicochemical properties of caseinate films were modified by the incorporation of gallic acid. Permeability and light barrier properties of the films were significantly affected by the incorporation of gallic acid. A maximum of 67% of gallic acid was released from the film with lowest gallic acid concentration. The DPPH antioxidant activity of food simulant solutions ranged between ∼40 and 80%. Oxidative enzyme inactivation by using phenolic compounds is a new concept in food packaging domain.